2018
DOI: 10.1159/000488817
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Enterocolitis in Two Siblings and an Unrelated Infant with Overlapping Chromosome 6q25 Deletions

Abstract: The pathogenesis of necrotizing enterocolitis (NEC) remains poorly understood but is thought to be multifactorial. There are no specific recurring chromosomal abnormalities previously associated with NEC. We report 3 cases of intestinal necrosis associated with large chromosome 6 deletions. The first patient was found to have a 7.9-Mb deletion of chromosome 6 encompassing over 40 genes, arr[GRCh37] 6q25.3q26(155699183_163554531)×1. The second patient had a 19.5-Mb deletion of chromosome 6 generated by an unbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first case of NOMI diagnosed by clinical and histopathological findings in a pediatric patient with interstitial 6q25 microdeletion syndrome. Regarding the reports of intestinal inflammation in patients with Coffin–Siris or 6q25 microdeletion syndrome, three cases of necrotizing enterocolitis in children with chromosome 6q25 deletions have been reported 4 . The authors speculated that the EZR gene, which was also deleted in this patient, can be a predisposing factor of intestinal vulnerability.…”
Section: Figmentioning
confidence: 85%
“…To the best of our knowledge, this is the first case of NOMI diagnosed by clinical and histopathological findings in a pediatric patient with interstitial 6q25 microdeletion syndrome. Regarding the reports of intestinal inflammation in patients with Coffin–Siris or 6q25 microdeletion syndrome, three cases of necrotizing enterocolitis in children with chromosome 6q25 deletions have been reported 4 . The authors speculated that the EZR gene, which was also deleted in this patient, can be a predisposing factor of intestinal vulnerability.…”
Section: Figmentioning
confidence: 85%
“…Chromosome 6: NEC-like intestinal necrosis had been described in two infants and in one neonate that was full-term or near fullterm born by Esdal et al 16 All three cases shared a deletion on chromosome 6 in the region 6q25.3 to q26. One of the infants had a deletion on chromosome 6, while one of the infants and the neonate were siblings and had identical unbalanced chromosome 6 to chromosome 18 translocations resulting in the loss of genetic material from chromosome 6.…”
Section: Relationship Between Structural Chromosomal Disorders and Necmentioning
confidence: 89%
“…These results indicated that HBM-exos were more focused on regulating biological processes of growth and development. It has been documented that genetic variation in chromosomes is associated with an increased risk of NEC [ 37 , 38 ]. Our results and those of previous studies indicate that HBM-exos have good prospects for NEC caused by genetic metabolism or abnormal growth and development.…”
Section: Discussionmentioning
confidence: 99%